Characterization and selection of endophytic actinobacteria for growth and disease management of Tea (Camellia sinensis L.) - Hazarika, Shabiha Nudrat; Saikia, Kangkon; Thakur, Debajit (Frontiers in Plant Science, 2022)
Endophytic microbes are vital for nutrient solubilization and uptake, growth, and survival of plants. Here, 88 endophytic actinobacteria (EnA) associated with five tea clones were isolated, assessed for their diversity, plant growth promoting (PGP), and biocontrol traits, and then used as an inoculant for PGP and disease control in host and non-host plants. Polyphasic methods, including phenotypic and genotypic characteristics, led to their identification as Streptomyces, Microbacterium, Curtobacterium, Janibacter, Rhodococcus, Nocardia, Gordonia, Nocardiopsis, and Kribbella. Out of 88 isolates, 35 (39.77%) showed antagonistic activity in vitro against major fungal pathogens, viz. Fusarium oxysporum, Rhizoctonia solani, Exobasidium vexans, Poria hypobrunnea, Phellinus lamaensis, and Nigrospora sphaerica. Regarding PGP activities, the percentage of isolates that produced indole acetic acid, siderophore, and ammonia, as well as P-solubilisation and nitrogen fixation, were 67.05, 75, 80.68, 27.27, 57.95, respectively. A total of 51and 42 isolates showed chitinase and 1-aminocyclopropane-1-carboxylic acid deaminase activity, respectively. Further, two potent Streptomyces strains KA12 and MA34, selected based on the bonitur scale, were screened for biofilm formation ability and tested in vivo under nursery conditions. Confocal laser scanning microscopy and the crystal violet staining technique revealed that these Streptomyces strains can form biofilms, indicating the potential for plant colonization. In the nursery experiment, they significantly enhanced the shoot and root biomass, shoot and root length, and leaf number in host tea plants. Additionally, treatment of tomato seeds by KA12 suppressed the growth of fungal pathogen Fusarium oxysporum, increased seed germination, and improved root architecture, demonstrating its ability to be used as a seed biopriming agent. Our results confirm the potential of tea endophytic actinobacterial strains with multifarious beneficial traits to enhance plant growth and suppress fungal pathogens, which may be used as bioinoculant for sustainable agriculture.